Top secret when our government keeps us in the dark - Stone, Geoffrey R. (Free expression in America series, 2007)
Explores whether the measures taken and suggested by the executive branch of the United States government to prevent and punish public disclosure of classified information are consistent with the First Amendment of the Constitution.